NATIONAL AND INTERNATIONAL DIMENSION IN INDONESIA’S EXCLUSIVE ECONOMIC ZONE - Ida Kurnia; Imelda Martinelli (Fakultas Hukum Universitas Gadjah Mada, 2017)
With both national and international dimensions influencing the utilization of marine fisheries resources in Indonesia’s Exclusive Economic Zone, a comprehensive regulation is needed. Hence the importance of making sure that National Regulations are in accordance with International Regulations, while still maintaining the best of interests for the people and accommodating for the people’s welfare. In reality, international community depends heavily on natural marine fisheries resources for their people’s nutrients need.